2022
DOI: 10.1136/bmj-2021-069620
|View full text |Cite
|
Sign up to set email alerts
|

Fever therapy in febrile adults: systematic review with meta-analyses and trial sequential analyses

Abstract: ObjectiveTo investigate the effects of fever therapy compared with no fever therapy in a wide population of febrile adults.DesignSystematic review with meta-analyses and trial sequential analyses of randomised clinical trials.Data sourcesCENTRAL, BIOSIS, CINAHL, MEDLINE, Embase, LILACS, Scopus, and Web of Science Core Collection, searched from their inception to 2 July 2021.Eligibility criteriaRandomised clinical trials in adults diagnosed as having fever of any origin. Included experimental interventions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
0
9
0
3
Order By: Relevance
“… 21 More broadly, a recent systematic review of fever therapy in febrile adults found insufficient evidence to confirm or refute any benefit in quality of life. 22 These results do not, however, exclude the potential benefit of hypothermia in subgroups such as patients with non-shockable rhythms and those with cardiogenic shock. 8 , 23 …”
Section: Discussionmentioning
confidence: 95%
“… 21 More broadly, a recent systematic review of fever therapy in febrile adults found insufficient evidence to confirm or refute any benefit in quality of life. 22 These results do not, however, exclude the potential benefit of hypothermia in subgroups such as patients with non-shockable rhythms and those with cardiogenic shock. 8 , 23 …”
Section: Discussionmentioning
confidence: 95%
“…31,32,34,35 A recent meta-analysis by Holgersson and colleagues concluded that fever therapy does not seem to affect mortality, and does not have serious adverse events. 36 The effects of commonly used antipyretics, such as nonsteroidal anti-inflammatories (NSAID) and paracetamol, on fever and functional outcome seem to be modest or non-existent, whereas NSAIDs are associated with increased bleeding risks and renal toxicity, and paracetamol in high doses can cause liver toxicity. 25,37,38 Furthermore, a recent study by Hassager and colleagues showed that prolonged device-based prevention of fever for 72 h did not improve the functional outcome compared to 36-h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fever as a protective mechanism in sepsis has been indicated, and it appears that spontaneous normothermia or mild hypothermia may be an ominous sign 31,32,34,35 . A recent meta‐analysis by Holgersson and colleagues concluded that fever therapy does not seem to affect mortality, and does not have serious adverse events 36 . The effects of commonly used antipyretics, such as nonsteroidal anti‐inflammatories (NSAID) and paracetamol, on fever and functional outcome seem to be modest or non‐existent, whereas NSAIDs are associated with increased bleeding risks and renal toxicity, and paracetamol in high doses can cause liver toxicity 25,37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Mehr als die Hälfte der untersuchten Patienten unterlag dabei einer kritischen Erkrankung. Die Studie untersuchte sowohl eine medikamentöse als auch eine physikalische Kühlung und schloss ebenfalls infektiöse sowie nicht infektiöse Ursachen für das Fieber mit ein [40].…”
Section: Merkeunclassified